Al content-dependent resistive switching in Al-rich AlOxNy thin films - Zhu, W. (2015)
Resistive switching can occur in Al-rich AlO x N y thin films depending on the Al content, i.e., the films with a small Al content exhibit resistive switching, but no resistive switch is observed in the films with a large Al content. The forming voltage, set/reset voltages, currents at the low- and high-resistance states, and conduction behavior of the low-resistance state are found to be dependent of the Al content. The phenomena can be explained by the changes in the complete filaments that consist of the metallic filaments formed by Al nanophases and the non-metallic filaments formed by oxygen vacancies.